Increasing Academic Performance on Earth Science Among Grade 9 Learners through Developed Self-Learning Materials - Aquino, Eugene Jay (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigated the effectiveness of utilizing self-learning modules as a tool in increasing academic performance in Earth Science among Grade 9 learners. The researcher used purposive sampling, choosing 18 respondents as experimental group that are subjected to the intervention. Using paired t-test and Mean Percentage Scores, the pre-test scores of the students are described as Moving Towards Mastery. The post-test scores of the students may be described as Closely Approximating Mastery by the interpretation of the scores of DepEd (2012) under Memorandum No. 160. It showed that the experimental group for the pre-test and post-test got 0.001 which is lesser than 0.05, this indicates that the students’ performance was better than the pre-test after using developed self-learning materials